SYNERGIZING SOCIAL SERVICE POLICY AND MANAGEMENT FOR POVERTY ALLEVIATION - Meiti Subardhini (Adisam Publisher, 2025)
Cross-sector cooperation and a synergy between social service administration and public policy are necessary to reduce poverty. The purpose of this essay is to pinpoint the elements that make government, business, and civil society collaboration on poverty reduction initiatives successful. Research shows that for social programmes to be effective, new approaches are needed, such as digital technology and community-based methodologies, together with cross-level cooperation and policy alignment. The private sector offers capital and access to markets, while the public sector plays the role of regulator and enabler. Civil society mentors and empowers the community. This synergy is impeded by bureaucratic red tape, limited local competency, and policy fragmentation. However, the adoption of integrated information systems and strategic partnerships with cross-sector stakeholders may improve the long-term viability of social services and programme effectiveness. To ensure poverty reduction synergies, this study recommends harnessing digital innovation, improving human resource capabilities, and strengthening cross-sector cooperation. With long-term and effective partnerships, social activities are expected to dramatically increase community welfare and reduce extreme poverty in Indonesia.